The indicators of physical development of children with Cerebral Palsy as the basis of differential approach to implementation of the physical rehabilitation program of using Bobath-therapy method - Kashuba, Vitaliy; Bukhovets, Bozhena (Journal of Education, Health and Sport, 2017)
Despite the existence of traditional and diverse ranges of author approaches for physical rehabilitation, there is still a problem of choosing and applying the most effective methods.The physical development as a complex characteristic is one of the leading assessments of the morpho-functional state of children in it`s development and in the process of growth. An important component of the child's development is the structure of the body, which is characterized by a number of anthropometric parameters that determine the features of sizes proportionality, indicating the physiology of the musculoskeletal, muscular, nervous and other systems of the body, as well as signaling the development of the child's pathology.Results of the study. The purpose of this study is to determine the effect of the physical therapy using the Bobat-therapy on the parameters of physical development in preschool children with Cerebral Palsy.The main indicators of physical development in children with Cerebral Palsy include body weight (BW, kg), body length standing (BL, cm) and sitting (BLS, cm), head coverage (HC, cm), chest coverage (CC, cm) and its excursion (CE, cm). Other indicators of physical evolution have not been widely used in practice. All indicators of physical development have been investigated using traditional methods.For the determination of children’s with Cerebral Palsy physical development with lesions we examined influence of the physical rehabilitation using the Bobat-therapy, 35 children aged 4.1 ± 1.1 years (at the beginning of the course).That was the main group (MG). We conducted all of 72 procedures. There was also a control group (CG), wher the results of physical development were studied and analyzed in 34 children aged 3.8 ± 0.9 years who were undergoing rehabilitation using standard methods.The course of Bobat-therapy included: the provision of treatment using specialized child's body position, the reduction of the influence of pathological reflexes (ASSHT, lip reflex (snot reflex), sucking, search, Moreau, cross extensor reflex, etc.) on the musculoskeletal system and implementation of the complex of exercises for the formation of elementary motor skills and the development of basic physical qualities.Conclusions. Studies of the dynamics of the physical development indicators of children with Cerebral Palsy were carried out using Bobat-therapy during 6 months. It was shown that after 6-month physical rehabilitation using Bobat-therapy, in comparison with standard approaches, there was an increase in physical development indices of children, in particular, body length (p <0.05), body weight (p <0.01) and circumference thorax (p <0.05).